RESPON SISWA TERHADAP MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA PADA MATERI PEWARTAAN KELAS XI DI SMA DON BOSCO SANGGAU - Amonius Amonius; Aloysius Mering; Eny Enawaty (Bahasa Indonesia, 2021)
This study aims to know students' response to the aspect of attraction, materials and attention to multimedia study-based learning materials on don bosco sanggau high school in reporting materials. Research uses descriptive methods with a qualitative approach. The data-gathering technique used was indirect communication. The data-collection tool used was an angket sheet. The data analysis techniques used in this study are data reductions, data presentation and deduction drawing. Research shows that don bosco's high school student response rates on multimedia study-based learning materials include an average interest aspect of 90.60%, material 89.20% and attention content 95%. The conclusion of the study is that students' response to the aspect of attraction, materials and attention to multimedia study-based learning in reporting materials on don bosco's high school has very good criteria.